Effectiveness of within-session practice distribution schedules on the basketball shooting ability of college students - Reña, Cyd Joaqxz DP. 2002-
Practice distribution schedules are a way of enhancing the efficiency of learning a new skill for any individual. Massed practice is where the rest time is shorter than the practice time, while distributed practice involves the rest time being longer or equal to the practice time (Promethean, 2023). The literature shows inconsistent findings between the results of massed and distributed practice across multiple fields, with the relationship between practice distribution schedules and the shooting ability in basketball rarely being explored. Sixteen non-player college students with no prior injuries participated. Ethical clearance was obtained before the start of the experimentation process. The participants underwent a three-week training program using different practice schedules. Acquisition and retention tests were used to measure the participants’ performance. Independent t-tests were used to analyze the data. Results showed that there was no significant difference between the acquisition test and retention test scores of the two groups (all p > 0.05), as well as the pre-test and retention test scores of each group respectively (p = 0.94, 0.76, 0.13, 0.16). These results follow the trend of the literature from Novak (1980) and Ford (1972). Factors such as environmental conditions (Sawka et al., 2016) and the learning plateau theory (Basiouny, 2016) explain why there is no statistically significant difference between massed practice and distributed practice.